UNELE CONSIDERAȚIUNI PRIVIND ROLUL DRONEI ÎN ASIGURARE A SECURITĂȚII FRONTIEREI NAȚIONALE - Buzev, Anatol; Cebotari, Svetlana (My University, 2019)
The technical and scientific progress has led to the development of new and advanced remote-controlled aircraft. In this context, drones are as well recent elaboration. Currently, drones can be operated to ensure security, including for the purpose of national border security. The presen article aims to underline the role of the drones in ensuring the control of the state border of the Republic of Moldova.
Keywords: frontiera de stat; securittatea frontierei de stat